2022
DOI: 10.1186/s12917-021-03105-3
|View full text |Cite
|
Sign up to set email alerts
|

Sophorolipid protects against early-weaning syndrome by improving the gut microenvironment in early-weaned piglets

Abstract: Background In animals, weaning stress is the first and most critical stress. Weaning can negatively affect the growth performance of animals physically, psychologically, and pathologically. Our previous studies on the HT-29 cell line and early-weaned rats demonstrated that adequate sophorolipid (SPL) supplementation in feed could enhance the mucin-producing and wound healing capacities of the gut defense system by modulating gut microbiota. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Weaning influences the intestinal mucosal immunity and growth performance of pigs ( 20 ). Intestinal mucosal immunity is an important factor for the intestinal development of pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Weaning influences the intestinal mucosal immunity and growth performance of pigs ( 20 ). Intestinal mucosal immunity is an important factor for the intestinal development of pigs.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, dietary SPL supplementation quadratically increased SCFA production at high concentrations of propionate and butyrate. Our previous studies also showed that SPL-supplemented feed could enhance SCFA concentrations by modulating the gut microbiota population in diverse animal models [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%